Narrativas de una madre sobre la experiencia de la pérdida de un hijo como consecuencia de ejecuciones extrajudiciales. (2023)
This study was conducted under an interdisciplinary perspective, qualitative with a narrative design, which aims to describe the narratives on the experience of the loss of a child as a result of extrajudicial executions. A mother who went through the scenario of the armed conflict in Colombia participated in the study.